KCa1.1 is potential marker for distinguishing Ah-type baroreceptor neurons in NTS and contributes to sex-specific presynaptic neurotransmission in baroreflex afferent pathway. (14th September 2015) - Zhang, Yu-Yao; Yan, Zhen-Yu; Qu, Mei-Yu; Guo, Xin-Jing; Li, Guo; Lu, Xiao-Long; Liu, Yang; Ban, Tao; Sun, Hong-Li; Qiao, Guo-Fen; Li, Bai-Yan
Highlights: KCa1.1 mediates the afferent-specific neurotransmission in NTS in both male and female rats. Increased glutamate release is seen in C- not A-type afferents by blocking KCa1.1 in male rats. ∼50% capsaicin-insensitive afferents are myelinated Ah-type BRNs in NTS in female rats. C-like KCa1.1-mediated glutamate release can also be seen in Ah-type BRNs in female NTS. KCa1.1 functional expression is a potential maker for identifying Ah- from A-type afferent in NTS. Abstract: Sexual-dimorphic neurocontrol of circulation has been described in baroreflex due largely to the function of myelinated Ah-type baroreceptor neurons (BRNs, 1st-order) in nodose. However, it remains unclear if sex- and afferent-specific neurotransmission could also be observed in the central synapses within nucleus of solitary track (NTS, 2nd-order). According to the principle of no mixed neurotransmission among afferents and differentiation of Ah- and A-types to iberiotoxin (IbTX) observed in nodose, the 2nd-order Ah-type BRNs are highly expected. To test this hypothesis, the excitatory post-synaptic currents (EPSCs) were recorded in identified 2nd-order BRNs before and after IbTX using brain slice and whole-cell patch. These results showed that, in male rats, the dynamics of EPSCs in capsaicin-sensitive C-types were dramatically altered by IbTX, but not in capsaicin-insensitive A-types. Interestingly, near 50% capsaicin-insensitive neurons in females showed similar effects to C-types, suggesting the existence of Ah-types in NTS, which may be the likely reason why the females had lower blood pressure and higher sensitivity to aortic depressor nerve stimulation via KCa1.1-mediated presynaptic glutamate release from Ah-type afferent terminals.